Kepastian Hukum dalam Penjatuhan Tindakan Atas Dasar Keadaan Pribadi Anak - Delviola Azhara; Ade Adhari (Syntax Literate, 2023)
The purpose of this research is to find out how Law Number 11 of 2012 concerning the Juvenile Criminal Justice System regulates the imposition of measures on children who commit criminal offenses based on the child's personal circumstances. The research method used is normative juridical method with statutory approach. The personal circumstances of children can be used as a basis for judges' consideration not to impose criminal sanctions, but not as an excuse that can justify themselves in violating the law. Until now, the personal circumstances of children still exist as part of the reasons for criminal punishment. The legal certainty of the child's personal circumstances as the imposition of sanctions is important to provide justice to children who are perpetrators of criminal acts, that children who have (conditions) personal circumstances at the time of the act can be used as a basis for judges not to impose criminal sanctions by considering aspects of justice and humanity.